Assessment of Levels of Some Biochemical Compounds in Patients with Chronic Kidney Disease - Noor Taha Yassin; Mohanad Hasan Mahmood Al-Izzi (Institute of Educational, Research, and Community Service, 2024)
Biomarker studied for chronic kidney disease are continuing. Uric acid and glutathione are biomarkers that have been studied and shown to have a variety of impacts. The aim of this study was to evaluate the Biochemical Compounds levels of patients with chronic kidney disease. The present research utilized a group of 30 male and female participants who were considered to be in optimal health to serve as the study's control group. In addition, a group of 60 male and female patients with Chronic kidney disease. The study found that patients with Chronic kidney disease had significantly higher levels of Uric acid than healthy controls and a highly significant levels of glutathione difference between the two groups.